Effect of drywall and brick wall on fire behavior of concrete‐filled steel tube column. (9th October 2017) - Abdollahzadeh, Gholamreza; Afaghi‐Darabi, Alireza
Abstract : The walls around the columns play a decisive role in temperature distribution and mechanical behavior of the column under fire. This study has been conducted to investigate the effects of the presence of two types of walls, including clay masonry wall and dry wall on temperature distribution, and mechanical behaviors of the column compared to the adiabatic condition. A three‐dimensional finite element model was developed and validated using the experimental results of the column under the non‐uniform fire. In this state, three different wall locations around the columns were considered. In modeling clay masonry wall, the thermal properties of the brick block and the cement mortar and in dry wall modeling the thermal properties of Gypsum panel and the applied insulator were extracted from the prior research. The outputs of the model consist of temperature distribution in the cross section of the wall and the column, fire resistance time, and residual strength of the column. The results of the research showed that the presence of brick and dry walls, under the best conditions, increases the resistance time to 46 and 53%, respectively, and residual strength of concrete‐filled steel tube to 27% as compared to the adiabatic condition.